2023
DOI: 10.3390/genes14061232
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification with Dimethyl Sulfoxide Induces Transcriptomic Alteration of Gene and Transposable Element Expression in Immature Human Oocytes

Abstract: Despite substantial advancements in the field of cryobiology, oocyte and embryo cryopreservation still compromise developmental competence. Furthermore, dimethyl sulfoxide (DMSO), one of the most commonly used cryoprotectants, has been found to exert potent effects on the epigenetic landscape of cultured human cells, as well as mouse oocytes and embryos. Little is known about its impact on human oocytes. Additionally, few studies investigate the effects of DMSO on transposable elements (TE), the control of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…We evaluated its mRNA level after exposure to cryopreservation and different IVM systems. The low level of DNMT3A in immCOCs that we obtained is consistent with the results described previously, which demonstrated a general decrease in transcription at the end of the oocytes’ growth phase and during the transition to meiotic competence [ 35 ]. This is evolutionarily possible due to the accumulation of stable mRNA at the beginning of oocytes’ development, which becomes a reservoir for their further use to support the oocytes’ maturation and embryogenesis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We evaluated its mRNA level after exposure to cryopreservation and different IVM systems. The low level of DNMT3A in immCOCs that we obtained is consistent with the results described previously, which demonstrated a general decrease in transcription at the end of the oocytes’ growth phase and during the transition to meiotic competence [ 35 ]. This is evolutionarily possible due to the accumulation of stable mRNA at the beginning of oocytes’ development, which becomes a reservoir for their further use to support the oocytes’ maturation and embryogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…This is evolutionarily possible due to the accumulation of stable mRNA at the beginning of oocytes’ development, which becomes a reservoir for their further use to support the oocytes’ maturation and embryogenesis. Silencing of transcriptional activity is believed to begin in the GV phase and is not fully reversed until fertilization [ 35 ]. Our work showed that the mRNA level of DNMT3A was significantly higher in DOs regardless of the effect of cryopreservation.…”
Section: Discussionmentioning
confidence: 99%